Relocating Aborigines in Sally Morgan’s My Place - Azimullah (University of Chitral Journal of Linguistics and Literature, 2018)
Sally Morgan’s novel My Place explicitly portrays the resistance of Aborigines subalterns against the prevailing social, economic, cultural and political issues. Focusing on identity, hybridity, ethnicity, and racism, the paper argues how Aborigines undergo social injustice, racial distortion, class disparity and adversarial displacement by Neo-colonialism. Investigating the Aborigines’ academic endeavours, genealogical suppressive destitutions, groundbreaking reattachment, matrilineal links, it is hypothesized that My Place foregrounds the contemporary status of modern Aboriginal Woman. Illustrating the Aborigines’ altruistic patriotism and excruciating their sufferings during Neo-colonialism in the novel, it is spotlighted how lost generation and stolen generation and extortive afflictions imposed on the Aborigines by the Whites in Australia have shaped the formers’ collective socio-cultural and political consciousness.